CD206+ tendon resident macrophages and their potential crosstalk with fibroblasts and the ECM during tendon growth and maturation - Bautista, Catherine A.; Srikumar, Anjana; Tichy, Elisia D.; Qian, Grace; Jiang, Xi; Qin, Ling; Mourkioti, Foteini; Dyment, Nathaniel A. (Frontiers in Physiology, 2023)
Resident macrophages exist in a variety of tissues, including tendon, and play context-specific roles in their tissue of residence. In this study, we define the spatiotemporal distribution and phenotypic profile of tendon resident macrophages, and their crosstalk with neighboring tendon fibroblasts and the extracellular matrix (ECM) during murine tendon development, growth, and homeostasis. Fluorescent imaging of cryosections revealed that F4/80+ tendon resident macrophages reside adjacent to Col1a1-CFP+ Scx-GFP+ fibroblasts within the tendon fascicle from embryonic development (E15.5) into adulthood (P56). Through flow cytometry and qPCR, we found that these tendon resident macrophages express several well-known macrophage markers, including Adgre1 (F4/80), Mrc1 (CD206), Lyve1, and Folr2, but not Ly-6C, and express the Csf1r-EGFP (“MacGreen”) reporter. The proportion of Csf1r-EGFP+ resident macrophages in relation to the total cell number increases markedly during early postnatal growth, while the density of macrophages per mm2 remains constant during this same time frame. Interestingly, proliferation of resident macrophages is higher than adjacent fibroblasts, which likely contributes to this increase in macrophage proportion. The expression profile of tendon resident macrophages also changes with age, with increased pro-inflammatory and anti-inflammatory cytokine expression in P56 compared to P14 macrophages. In addition, the expression profile of limb tendon resident macrophages diverges from that of tail tendon resident macrophages, suggesting differential phenotypes across anatomically and functionally different tendons. As macrophages are known to communicate with adjacent fibroblasts in other tissues, we conducted ligand-receptor analysis and found potential two-way signaling between tendon fibroblasts and resident macrophages. Tendon fibroblasts express high levels of Csf1, which encodes macrophage colony stimulating factor (M-CSF) that acts on the CSF1 receptor (CSF1R) on macrophages. Importantly, Csf1r-expressing resident macrophages preferentially localize to Csf1-expressing fibroblasts, supporting the “nurturing scaffold” model for tendon macrophage patterning. Lastly, we found that tendon resident macrophages express high levels of ECM-related genes, including Mrc1 (mannose receptor), Lyve1 (hyaluronan receptor), Lair1 (type I collagen receptor), Ctss (elastase), and Mmp13 (collagenase), and internalize DQ Collagen in explant cultures. Overall, our study provides insights into the potential roles of tendon resident macrophages in regulating fibroblast phenotype and the ECM during tendon growth.